DETERMINANT OF TYPE FINANCING ON ISLAMIC COMMERCIAL BANK’S PROFITABILITY - Hasyim, Fuad; Hidayat, Muhammad Fikri; Pangesti, Putri Ika (Indonesian Scientific Journal of Islamic Finance, 2024)
The purpose of this study is to analyze the effect of murabahah, mudharabah, musyarakah, and ijarah financing on Return On Assets (ROA) in Islamic Commercial Banks for the period 2016–2020. The population in this research was all Islamic Commercial Banks registered with Otoritas Jasa Keuangan for the period 2016–2020. Purposive sampling was used to obtain samples from the 12 banks. The results of the research show that the murabahah and mudharabah financing variables had an effect on Return On Assets. Meanwhile, musyarakah and ijarah financing had no effect on Return On Assets.